A first course in differential equations, modeling and simulation - Smith, Carlos A., 1943-; Campbell, Scott W. (CRC Press, Taylor & Francis Group, 2016)
A First Course in Differential Equations, Modeling, and Simulation shows how differential equations arise from applying basic physical principles and experimental observations to engineering systems. Avoiding overly theoretical explanations, the textbook also discusses classical and Laplace transform methods for obtaining the analytical solution of differential equations.